EDUCATIONAL METHODS IN SURAH AL-MUJADALAH - Achyar Zein; Yusnaili Budianti; Adlan Lufti Siregar; M. Fajri Syahroni Siregar (Pusat Penerbitan Universitas (P2U) Unisba, 2021)
The research that the researcher carried out included qualitative research and when collecting the data used the Book Research method. This data is presented in descriptive form in the form of sentences. The data in this study were collected and analyzed for validity from various sources. The results of this study stated